Feasibility of floating solar photovoltaic systems (FSPVs) development in Nigeria: an economic cost appraisal case study - Samuel Oliver Effiom (Applied Engineering and Technology, 2023)
This study focused on evaluating the economic cost viability of developing a floating solar photovoltaic systems (FSPVs) project in Nigeria, using Ikang river, Bakassi as an incident study. The FSPVs was designed using the HOMER software to satisfy full load requirements of 2426.45 kWh/day, while appraising the viability of the FSPVs in incident study. Meteorological data of the incident study location which include geographical coordinates, ambient temperature, and global horizontal irradiance were used to select a suitable FSPVs design for the cost appraisal. Lifecycle cost model was further developed to evaluate the proposed FSPVs at different project development phases. These include: predevelopment and consenting (PC), procurement and acquisition (PA), installation and commissioning (IC), operation and maintenance (OM), and decommissioning and disposal (DD). The results obtained showed that the net present cost, Levelized cost of energy, and operating cost of the project were 10,350,933.25USD, 0.90USD/kWh, and 179,164.73USD, respectively. Also, the capital expenditure (CAPEX) amassed by 81.53% of the entire project cost, while operating expenditure (OPEX) was 18.47%. Furthermore, installation, support systems, predevelopment and project management, contingencies, indirect cost, and electrical equipment were the key drivers of the project. For the lifecycle stages; PC, PA, IC, OM and DD were obtained to be 12%, 57.9%, 11.6%, 9.96%, and 8% respectively of the project cost. Thus, the incident study location has the potential for FSPVs development and has proven to be economically viable. Nevertheless, established model was suitable in appraising preliminary variations in FSPVs.